Service-oriented flexible and interoperable assessment: towards a standardised e-assessment system - AL-Smadi, M.; Guetl, Christian (Inderscience Enterprises Ltd, 2011)
Free-text answers assessment has been a field of interest during the last 50 years. Several free-text answers assessment tools underpinned by different techniques have been developed. In most cases, the complexity of the underpinned techniques has caused those tools to be designed and developed as stand-alone tools. The rationales behind using computers to assist learning assessment are mainly to save time and cost, as well as to reduce staff workload. However, utilising free-text answers assessment tools separately form the learning environment may increase the staff workload and increase the complexity of the assessment process. Therefore, free-text answers scorers have to have a flexible design to be integrated within the context of the e-assessment system architectures taking advantages of software-as-a-service architecture. Moreover, flexible and interoperable e-assessment architecture has to be utilised in order to facilitate this integration. This paper discusses the importance of flexible and interoperable e-assessment. Moreover, it proposes a service-oriented flexible and interoperable architecture for futuristic e-assessment systems. Nevertheless, it shows how such architecture can foster the e-assessment process in general and the free-text answers assessment in particular.